Estratégia corporativa da companhia Vale: especialização, investimento e internacionalização - Aleff Neivisson Ferreira Lopes (2022)
The so-called financialization or “maximizing shareholder value” (Maximizing Shareholder Value - MSV) refers to corporate behavior that seeks to raise the market value of companies and meet the interests of majority shareholders. Among the main practices attributed to MSV, the following stand out: (i) allocation of a significant part of the funds obtained to the payment of dividends; (ii) execution of share buyback programs; (iii) expansion of the remuneration of senior executives, generally linked to the performance of the company's stock price. In the operational scope, we can mention: (iv) decrease in Research and Development (R&D) expenses; (v) increase in leverage and indebtedness indicators; (vi) increased ownership of financial assets; (vii) reduction in the payback period on investments and expansion of liquidity preference and; (viii) increase in production capacity through acquisitions and mergers instead of investments in new production units, as a consequence, a bias towards oligopolization and productive specialization. In this context of a supposed financialized corporate strategy, the main objective of this dissertation was to evaluate whether the strategies adopted by the company Vale SA since its privatization can be considered financialized, or if they have taken other forms and consider other determinants. For this evaluation, the dissertation was divided into seven chapters. The first chapter surveys the literature on financialization and other corporate strategies, highlighting some of its constraints, as well as an empirical application for the case of Brazil, relating the total shareholders return to corporate practices considered financialized. The objective of this first part is to characterize the supposedly financialized corporate behavior and to associate indicators constructed from income statements, balance sheets and cash flow statements to it. Dealing specifically with Vale, the second chapter presents the period between 1996 and 1999, the post-privatization period, in which the Company's strategic guidelines were not yet well defined. The third chapter presents the time when Vale consolidated itself as a major international player in the iron ore industry and reached its highest market value in historical terms. The fourth chapter addresses the end of the commodities super cycle, when the Company was developing an ambitious investment plan, and saw its intention to internationalize constrained by both external and internal factors. The fifth chapter discusses the period between 2017 and 2021, where it was possible to observe corporate conduct considered financialized, especially after the decrease of the Federal Government's influence over the Company's controlling group and the subsequent edition of a new shareholder remuneration policy in 2018. The sixth chapter develops an empirical model that seeks to assess the determinants of Vale's market value based on indicators representing practices considered to be financialized. Finally, the seventh chapter sets out the main conclusions of this dissertation.